Association Between Substance Use and Periodontitis: A Cross-Sectional Analysis of NHANES Data on Marijuana, Hashish, and Cocaine - Aljoghaiman E (Clinical, Cosmetic and Investigational Dentistry, 2025)
Eman Aljoghaiman Department of Preventive Dental Science, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Eastern Province, Saudi ArabiaCorrespondence: Eman Aljoghaiman, Department of Preventive Dental Science, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Eastern Province, Saudi Arabia, Email ealjoghaiman@iau.edu.saPurpose: This study aimed to examine the association between the use of marijuana, hashish, cocaine, methamphetamine, and heroin with the severity of periodontal disease in adults.Patients and Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) 2011– 2012 and 2013– 2014 cycles, from 3609 participants, including demographic information, clinical examinations, and questionnaires. Key covariates assessed in the analysis included age, sex, race/ethnicity, education level, socioeconomic status, poverty/income ratio, marital status, occupation, alcohol consumption, body mass index (BMI), dental insurance coverage, and frequency of dental visits. Logistic regression models were employed to investigate the association between drug use and periodontitis, adjusting for potential confounders.Results: Among 3690 participants, 54% reported using marijuana or hashish, while 16% had tried cocaine, heroin, or methamphetamine. Marijuana or hashish use was significantly associated with severe periodontitis, affecting 39% of users (OR: 4.276; 95% CI: 3.682– 4.967; p = 0.001). Cocaine use was also linked to increased periodontitis, with most users presenting with mild disease. Alcohol consumption was positively associated with periodontitis (OR: 1.255; 95% CI: 1.066– 1.477; p = 0.006). No significant associations were found for heroin or methamphetamine use.Conclusion: Within the limitations of this study, marijuana, hashish, and cocaine users were found to have significantly higher odds of developing periodontitis. However, no clear relationship was established between the use of methamphetamine or heroin and periodontal disease. These findings suggest the need for public health interventions targeting substance users to mitigate the risk of periodontal disease.Keywords: periodontal disease, marijuana, hashish, cocaine, methamphetamine, NHANES